Constraining hadronization mechanisms with Λc+/D0 production ratios in Pb–Pb collisions at sNN=5.02 TeV - S. Acharya; D. Adamová; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; I. Ahuja; Z. Akbar; et al. (Physics Letters B, 2023)
The production of prompt Λc+ baryons at midrapidity (|y|<0.5) was measured in central (0–10%) and mid-central (30–50%) Pb–Pb collisions at the center-of-mass energy per nucleon–nucleon pair sNN=5.02 TeV with the ALICE detector. The results are more precise, more differential in centrality, and reach much lower transverse momentum (pT=1 GeV/c) with respect to previous measurements performed by the ALICE, STAR, and CMS Collaborations in nucleus–nucleus collisions, allowing for an extrapolation down to pT=0. The pT-differential Λc+/D0 ratio is enhanced with respect to the pp measurement for 4<pT<8 GeV/c by 3.7 standard deviations (σ), while the pT-integrated ratios are compatible within 1σ. The observed trend is similar to that observed in the strange sector for the Λ/KS0 ratio. Model calculations including coalescence or statistical hadronization for charm-hadron formation are compared with the data.